Status of Electricity Act, 2003: A systematic review of literature. (March 2017) - Mukherjee, Shilpi; Dhingra, Tarun; Sengupta, Anirban
Abstract: The Electricity Act 2003 was a landmark Act which promised to remove the maladies which afflict the Indian Power Sector and that too at a time when the sector was ridden with problems. With concepts such as open access, multiple distribution licensees, wheeling of electricity etc, the said Act intended to encourage competition which in turn was meant bring a paradigm shift in the sector. The paper undertakes a systematic literature review to find the status of review of the promising Act. More than a decade has passed since its enactment and amendments are due with the legislative body of India but none of the literature reviewed gives a comprehensive view encompassing all the objectives of the Act. Moreover, these documents study either the probable impact or the impact on a particular segment only. It has important implications for the Power sector which highlights a significant gap in literature and provides a basis on which future research can be built upon. Highlights: Electricity Act 2003 is a landmark in Indian power sector reform. Systematic literature review is done to find the status of review of the Act. Status of Electricity Act 2003 not comprehensively reviewed. Status of the act needs to be reviewed comprehensively through actual data.